The Effect Of Secang The Effect of Secang (Caesalpinia sappan) Masks on the Healing of Acne (Acne vulgaris) in Women Aged 21–25 Years Old - Maasyitoh Sari Latifah (Universitas Airlangga, 2023)
Introduction: Acne can be caused by the presence of acne-causing bacteria. Currently, various studies of acne treatment with herbal ingredients both topically and orally have been carried out with the aim of reducing acne-causing bacteria. Several studies have shown that the active compound of Secang, namely brazilin extracted with methanol and 50% ethanol in Propionibacterium acnes, has been shown to have anti-bacterial, lipase inhibitor, and antioxidant activity. So that researchers are interested in conducting research on